Estádio de Desenvolvimento do Milho. 2. Efeito sobre o Consumo e a Digestibilidade da Silagem em Ovinos - Lavezzo, OENM; Lavezzo, W.; deSiqueira, E. R. (Revista Sociedade Brasileira Zootecnia, 1997)
Corn plants were ensiled at the milk, milk-early dough, medium dough, and semi-hard dough stages. The intake and digestibility trials showed that: a) silage DM and NFE contents increased and ADF, cellulose, and lignin contents decreased with plant maturity; b) corn plant maturity had little effect on the digestibility of the silages, but the milk and medium dough stages produced the best results; c) no consistent effect of maturity was observed in DM and CP daily intakes (mean values 41.86 and 26.77/g/kg(75), respectively). Nevertheless, daily digestible dry matter and digestible protein intakes (g/kg(75)) were higher with medium-dough grains (31.74 and 1.97g, respectively) than with the milk (23.27 and 1.45g, respectively) and the milk-early dough stages (22.60 and 1.28g, respectively). However, similar intakes were observed with the medium-dough and semi-hard dough stages. Total digestible nutrient contents of the silages were affected little by corn plant maturity. Nevertheless, statistical differences were Found between the medium dough (70.09%) and the milk-early dough stages (63.07%).
Stage of corn development .2. Effect upon sheep voluntary intake and digestibility of the silage
Keywords: corn; digestibility; intake; maturity; silage